Nicotinic Acetylcholine Receptor Subunit Alpha-5 Promotes Radioresistance via Recruiting E2F Activity in Oral Squamous Cell Carcinoma - Lin, Che-Hsuan; Lee, Hsun-Hua; Kuei, Chia-Hao; Lin, Hui-Yu; Lu, Long-Sheng; Lee, Fei-Peng; Chang, Jungshan; Wang, Jia-Yi; Hsu, Kai-Cheng; Lin, Yuan-Feng (Journal of clinical medicine, 2019)
Radiotherapy is commonly used to treat patients with oral squamous cell carcinoma (OSCC), but a subpopulation of OSCC patients shows a poor response to irradiation treatment. Therefore, identifying a biomarker to predict the effectiveness of radiotherapy in OSCC patients is urgently needed. In silico analysis of public databases revealed that upregulation of CHRNA5, the gene encoding nicotinic acetylcholine receptor subunit alpha-5, is extensively detected in primary tumors compared to normal tissues and predicts poor prognosis in OSCC patients. Moreover, CHRNA5 transcript level was causally associated with the effective dose of irradiation in a panel of OSCC cell lines. Artificial silencing of CHRNA5 expression enhanced, but nicotine reduced, the radiosensitivity of OSCC cells. Gene set enrichment analysis demonstrated that the E2F signaling pathway is highly activated in OSCC tissues with high levels of CHRNA5 and in those derived from patients with cancer recurrence after radiotherapy. CHRNA5 knockdown predominantly suppressed E2F activity and decreased the phosphorylation of the Rb protein; however, nicotine treatment dramatically promoted E2F activity and increased Rb phosphorylation, which was mitigated after CHRNA5 knockdown in OSCC cells. Notably, the signature combining increased mRNA levels of CHRNA5 and the E2F signaling gene set was associated with worse recurrence-free survival probability in OSCC patients recorded to be receiving radiotherapy. Our findings suggest that CHRNA5 is not only a useful biomarker for predicting the effectiveness of radiotherapy but also a druggable target to enhance the cancericidal effect of irradiation on OSCC.